STRESS IN CHILDREN PATHOLOGY: FROM PSYCHOSOMATICS TO MOLECULAR BIOLOGY - Sorin Buzinschi (Amaltea Medical Publishing House, 2021)
During childhood, 3 levels of stress were proposed: positive, tolerable and toxic. The toxic stress produced by the strong, frequent and prolonged activation of the body's response systems is a generator of behavioral and somatic sequelae. Child abuse is present in all social media in different countries. The absence of basic care has devastating effects on social and cognitive development, as found in institutionalized children. Attachment behavior and fear memory are considered stress-related biological systems. The response to stress is driven by the dynamics of cortisol secretion and its interaction with its cellular receptor. It plays a central role in the response to aggression through the process of methylation, decreased gene expression in the hippocampus and increased response to stress. Stress treatment is variable in efficiency and involves preventive measures (family and community), at school, bullying, psychological counseling, trauma-focused psychotherapy, cognitive therapy, through music.